21. KELEMAHAN RESPON ASEAN INTERGOVERNMENTAL COMISSION ON HUMAN RIGHTS (AICHR) TERHADAP KASUS TENTARA ANAK DI MYANMAR 2010-2015 - Nimas Amasti, Atri Yuniar; Windiani, Reni; Paramasatya, Satwika (Journal of International Relations, 2016)
Myanmar is one of the biggest countries in the world who recruited children for child soldiers.The recruitment of child soldiers in Myanmar is recruited by Tatmadaw Kyi (Myanmarnational army). To resolve this case Myanmar signed Joint Action Plan (JAP) with UN in2012. But the efforts to resolve the case only came from international organizations whereasASEAN as regional organizations has a commission for human rights that is ASEANIntergovernmental Comission on Human Rights (AICHR). In AICHR work plan AICHRmentioned child soldiers issue for thematic studies of human rights. The aim of this researchis to analyze implementation of the work plan of child soldiers case in Myanmar. Thisresearch used literature study based of construtivism theory and correspondence with thestakeholder. Based on construtivism AICHR succeed to construct norms of human rights inASEAN region. Furthermore AICHR could not implemented the works plan in child soldierscase in Myanmar because of the hard mechanism to carried out that case. The mechanismrequire both representative of AICHR and Myanmar to carried out that case in AICHRsummit. Another reason for the failed implementation are the existence of non-interventionprincipal and weakness of protection function of AICHR.